Surgical implications of right aortic arch with isolation of left subclavian artery. Issue 9 (September 1975) - Rodriguez, L; Izukawa, T; Moës, C A; Trusler, G A; Williams, W G
Abstract : Few cases have been reported of the combination of right aortic arch with isolation of the left subclavian artery in childhood because of the absence of symptoms from this pairing of defects and the difficulty of its recognition by routine examination. All the reports have been associated with congenital heart disease. We report 4 cases. In one of them, the diagnosis was made during an attempt to create a left Blalock-Taussig anastomosis and the technique was modified. The diagnosis can be made before operation with an aortogram. This procedure should be carried out to show the aortic arch branches in cases where palliative surgery is contemplated.